Manufacturing Processes by Bonding Compression for Acoustic Composites: A Comprehensive Review - Basri, Hasan; Pranoto, Hadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2025)
Noise control is a growing concern in built environments, vehicles, and industrial machines. Porous multi-layer composite materials are currently the most used for this purpose. Some of them are felt-based materials widely utilized in acoustic applications due to their excellent sound absorption properties, flexibility, lightweight nature, and low manufacturing cost. Some synthetics & hybrid fiber materials are widely used for acoustic purposes. To optimize the acoustic performance, one of the materials, such as resinated felt, is commonly combined with nano-porous materials like spunbond, a PET-based non-woven material, as a skin layer due to their adjustable fiber structure and cost-effectiveness. Bonding compression techniques—including hot pressing, thermal bonding with low-melting fibers, and skin lamination spunbond are crucial in fabricating multi-layer acoustic composites from porous materials. This review synthesizes findings from studies detailing process parameters, material choices, and how compression affects porosity, fiber entanglement, and inter-layer bonding to optimize sound absorption. Special attention is given to the effects of processing parameters on porosity, air permeability, and fiber orientation—factors that critically influence acoustic behavior. Challenges such as frequency-dependent performance loss and scalability limits are discussed. Future research should target the development of the cycle optimization process and real durability evaluation.